Digital-Assisted Self-interview of HIV or Sexually Transmitted Infection Risk Behaviors in Transmasculine Adults: Development and Field Testing of the Transmasculine Sexual Health Assessment - Sari L Reisner; David R Pletta; Dana J Pardee; Madeline B Deutsch; Sarah M Peitzmeier; Jaclyn MW Hughto; Meg Quint; Jennifer Potter (JMIR Publications, 2023)
BackgroundThe sexual health of transmasculine (TM) people-those who identify as male, men, or nonbinary and were assigned a female sex at birth-is understudied. One barrier to conducting HIV- and sexually transmitted infection (STI)-related research with this population is how to best capture sexual risk data in an acceptable, gender-affirming, and accurate manner. ObjectiveThis study aimed to report on the community-based process of developing, piloting, and refining a digitally deployed measure to assess self-reported sexual behaviors associated with HIV and STI transmission for research with TM adults. MethodsA multicomponent process was used to develop a digital-assisted self-interview to assess HIV and STI risk in TM people: gathering input from a Community Task Force; working with an interdisciplinary team of content experts in transgender medicine, epidemiology, and infectious diseases; conducting web-based focus groups; and iteratively refining the measure. We field-tested the measure with 141 TM people in the greater Boston, Massachusetts area to assess HIV and STI risk. Descriptive statistics characterized the distribution of sexual behaviors and HIV and STI transmission risk by the gender identity of sexual partners. ResultsThe Transmasculine Sexual Health Assessment (TM-SHA) measures the broad range of potential sexual behaviors TM people may engage in, including those which may confer risk for STIs and not just for HIV infection (ie, oral-genital contact); incorporates gender-affirming language (ie, genital or frontal vs vaginal); and asks sexual partnership characteristics (ie, partner gender). Among 141 individual participants (mean age 27, SD 5 years; range 21-29 years; n=21, 14.9% multiracial), 259 sexual partnerships and 15 sexual risk behaviors were reported. Participants engaged in a wide range of sexual behaviors, including fingering or fisting (receiving: n=170, 65.6%; performing: n=173, 66.8%), oral-genital sex (receiving: n=182, 70.3%; performing: n=216, 83.4%), anal-genital sex (receptive: n=31, 11.9%; insertive: n=9, 3.5%), frontal-genital sex (receptive: n=105, 40.5%; insertive: n=46, 17.8%), and sharing toys or prosthetics during insertive sex (n=62, 23.9%). Overall barrier use for each sexual behavior ranged from 10.9% (20/182) to 81% (25/31). Frontal receptive sex with genitals and no protective barrier was the highest (21/42, 50%) with cisgender male partners. In total, 14.9% (21/141) of participants reported a lifetime diagnosis of STI. The sexual history tool was highly acceptable to TM participants. ConclusionsThe TM-SHA is one of the first digital sexual health risk measures developed specifically with and exclusively for TM people. TM-SHA successfully integrates gender-affirming language and branching logic to capture a wide array of sexual behaviors. The measure elicits sexual behavior information needed to assess HIV and STI transmission risk behaviors. A strength of the tool is that detailed partner-by-partner data can be used to model partnership-level characteristics, not just individual-level participant data, to inform HIV and STI interventions.